Microcarriers for tissue engineering applications - Balamuralidhar, Vanniarajan (2013)
Polystyrene microcarriers (PS) were surface modified to improve their biocompatibility for invivo applications. The PS microcarriers were modified by carbene insertion method with functional groups aniline, hydroxyl, hexyl, phosphonate di-ester and glycol groups. FTIR analysis confirmed the presence of new surface functional groups for modified microparticles. Subsequently the protein adsorption and cell attachment efficacy of surface modified PS were analysed. The surface features were also investigated for any possible distinctness in characteristics such as contact angle, zeta potential and to ensure that the bulk characteristics such as degradation temperature, glass transition temperature are not altered. Results showed that bulk characteristics were unaffected by the surface modification, whereas surface properties such as zeta potential and contact angle, which are characteristics of hydrophobicity, surface potential have changed by a small degree. Surface modified microcarriers showed equally efficient level of protein adsorption and cell adhesion analogous to blank microcarriers. Thus results showed that the surface modification did not change the bulk characteristics, but needs to be improved to get enhanced cell attachment and protein adsorption than unmodified microcarriers.